شێوە و پێکهاتەیێن هایبێردزێشنا زمانی د تێکستێ ئەدەبیدا - ڕومانا "ژانێن سیناهیێ" - وەکو نموونە - MOHAMMED, HAMDIYA HASSAN (Journal of Duhok University, 2023)
In this study, we dealt with the phenomenon of linguistic hybridization and consciousness in the novel "Zhanin Sinahiya" in the light of the theory of (Mikhail Bakhtin), which stipulates the mixing of two or more social languages in one linguistic word, which means the existence of two separate words in terms of time and consciousness performed by the speaker in the novel. This combination results in the convergence and dialogue of two eyes within the scope of the speaker's verbal pronunciation. Through the study, it was shown that the novelist uses linguistic hybridization in shaping the linguistic structure of his novelist text intentionally and unintentionally, because he wants his output to contain artistic and aesthetic values, to ensure its impact on the reader. And also in order to facilitate the process of communicating his experience and purposes. Because the hybrid language is the same language that is familiar and spoken among members of the community. In addition to political or cultural factors... Etc. Therefore, he has to use this language. The novelist was able to do so by relying on the mechanisms of the dialectical and the monologue. Thus, the presence of the phenomenon of hybridization in the novel is considered one of the manifestations of renewal and modernity in it, in terms of bringing together languages that belong to different societies from each other. The novel is one of the literary genres that continue to walk in the context of development and openness to multiple genres and arts, and because it has the flexibility characteristic of it, it has the ability to accommodate the changes of the times.